Three-Decades of Research Integration—Transforming to Collaborative Aquatic Food Systems Research Partnerships in the Pacific - Schwarz, Anne-Maree; Eriksson, Hampus; Ramofafia, Christain; Masu, Rosalie; Boso, Delvene; Govan, Hugh (Frontiers in Sustainable Food Systems, 2021)
High-quality research to provide sustainable development solutions in aquatic food systems requires a deliberate theory for its application at scale. One frequently defined pathway in theories of change for scaling research innovation is through partnerships. Yet, despite the widespread application of partnership modalities in food-systems research, only a small proportion of published research provides original and high-quality solutions for small-scale producers. Metrics of academic success can incentivize publication regardless of end-user impact. Analogously, partnerships among national and international institutions can also lack impact because of inequity and persistent power imbalances. We describe long-term research for development partnership between a CGIAR center (WorldFish) and a national government agency (Solomon Islands Ministry of Fisheries and Marine Resources; MFMR). We review the literature produced by, or about, the activities carried out in the name of the partnership over a 35-year period to build a time-line and to identify elements of research power, priorities and capacity by decade. The form and function of the collaboration through time form the basis of our analysis of the journey towards an increasingly equitable partnership: a theorized goal towards greater development outcome at scale in Solomon Islands. The partnership has been strongly influenced by changes in both institutions. The MFMR has undergone a significant increase in operational capacity since the partnership was first conceived in 1986. WorldFish has also undergone change and has navigated tensions between being locally impactful and globally relevant through periods of different research foci. With an increasingly competent and capable ministry, dimensions of power and practice have had to be re-visited to embed CGIAR research on aquatic food systems within national development trajectories. By focusing on a practice seeking more meaningful and respectful partnerships, WorldFish – as an international research partner – continues to evolve to be fit for purpose as a credible and effective research partner. We discuss this journey in the context of system-level change for aquatic food system sustainability and innovation.